The effect of Mercedes model with embedded assessment strategy and technology on biology students’ learning outcomes in Lagos Nigeria - OLADIPO, ADENIKE JULIANAH; Adewumi, Olusoji Olurotimi; Ogundiwin, Akinleye Oluyemi (Annual Journal of Technical University of Varna, 2019)
Abstract Methods and strategies traditionally used in teaching science have been described by several researchers as being unsatisfactory and ineffective over many years.  Hence, this study examined the effect of Mercedes Model with Embedded Assessment Strategy and Technology on Biology students’ learning outcomes. A pretest-post-test control group, quasi experimental design was adopted for the study.  Two purposively selected EDs were randomly assigned to experimental and control groups. Three senior secondary schools were randomly selected from each ED. Altogether, a total of six schools in the two selected EDs were involved in the study. Two intact classes (one science and another non-science) were randomly selected from each of the six schools making a total of twelve classes. In all 568 Senior Secondary Class I biology students formed the sample size. Five instruments were used to generate data for the study, namely, Mercedes Model with Embedded Assessment Strategy and Technology in Diffusion (M2EASTID), Mercedes Model with Embedded Assessment Strategy and Technology in Osmosis (M2EASTIO). Conventional Lesson Plan on Diffusion (COLPOD), Conventional Lesson Plan on Osmosis (COLPO) and Test on Students’ Learning Outcomes in Osmosis and Diffusion (TESLOOD). Four hypotheses were formulated and tested at 0.05 level of significance. Data collected were analysed using frequency counts, means, deviation and analysis of covariance.  There was significant effect of treatment on students’ learning outcomes on selected biology concepts. Also, subject specialization has a significant effect on the dependent measures. Mercedes Model with Embedded Assessment Strategies and Technology therefore was effective and significantly improved students’ learning outcomes. Hence, it was recommended that biology teachers in senior secondary schools should adopt Mercedes Model with Embedded Assessment Strategy and Technology for teaching for understanding and application of biology concepts.